Spanish seamen (circular) - Tewson, Vincent
025-0027-001 Telegraphic Address: TRADUNIC, SOWEST, LONDON. Telephone: Victoria 9020. Trades Union Congress GENERAL SECRETARY SIR WALTER CITRINE KBE To whom all communications should be addressed. Department International Our ref. HVT/AC/RC/328. Your ref. TRANSPORT HOUSE, SMITH SQUARE, LONDON, S.W.1. 19th January, 1940. SPANISH SEAMEN. It has come to our knowledge that, in isolated cases, offers of employment at sea have been declined in present circumstances by some of the Spanish seamen in our charge. Perhaps our circular of 21st December may have given rise to the impression that the possibilities of employment on land are greater than they in fact are. It may be relevant for the men to know that employment at sea on neutral vessels (in which openings are daily becoming more frequent) entails less risk than on British boats, and is remunerated at very good rates of pay. In the interests of the men, it is imperative that they find work soon, and we are naturally interested in any obstacles which may present themselves in the accomplishment of this aim. It might be useful if you could invite any men who would like to discuss the matter with you to air their viewpoint on it and let us know of circumstances which have deterred any seaman from accepting any employment offered if such a case exists in your area. Yours sincerely, H. V. TEWSON. Assistant Secretary. 292/946/25b/23